A preliminary study: Effects of football training on glucose control, body composition, and performance in men with type 2 diabetes. (5th June 2014) - Andersen, T. R.; Schmidt, J. F.; Thomassen, M.; Hornstrup, T.; Frandsen, U.; Randers, M. B.; Hansen, P. R.; Krustrup, P.; Bangsbo, J.
Abstract : The effects of regular football training on glycemic control, body composition, and peak oxygen uptake (VO2 peak) were investigated in men with type 2 diabetes mellitus (T2DM). Twenty‐one middle‐aged men (49.8 ± 1.7 years ± SEM) with T2DM were divided into a football training group (FG; n  = 12) and an inactive control group (CG; n  = 9) during a 24‐week intervention period (IP). During a 1‐h football training session, the distance covered was 4.7 ± 0.2 km, mean heart rate (HR) was 83 ± 2% of HRmax, and blood lactate levels increased ( P  < 0.001) from 2.1 ± 0.3 to 8.2 ± 1.3 mmol/L. In FG, VO2 peak was 11% higher ( P  < 0.01), and total fat mass and android fat mass were 1.7 kg and 12.8% lower ( P  < 0.001), respectively, after IP. After IP, the reduction in plasma glucose was greater ( P  = 0.02) in FG than the increase in CG, and in FG, GLUT‐4 tended to be higher ( P  = 0.072) after IP. For glycosylated hemoglobin (HbA1), an overall time effect ( P  < 0.01) was detected after 24 weeks. After IP, the number of capillaries around type I fibers was 7% higher ( P  < 0.05) in FG and 5% lower ( P  < 0.05) in CG. Thus, in men with T2DM, regular football training improves VO2 peak, reduces fat mass, and may positively influence glycemic control.